Poverty and Progress: Evaluating The Impact of Microfinance on Rural Economies in India - Kavitha, G. (Journal of Neonatal Surgery, 2025)
Microfinance has been extensively advocated as a mechanism for poverty reduction in rural India, characterized by prevalent financial exclusion and economic fragility. This research assesses the influence of microfinance on rural Indian economies, analyzing its impacts on household income, employment, women's empowerment, and social capital. The research employs a mixed-methods framework to examine household survey data from rural India (2015–2022) alongside qualitative case studies from Uttar Pradesh and Tamil Nadu. The results show that microfinance greatly increases income and business activity, especially for women. However, its effect on long-term poverty reduction and social empowerment is restricted by excessive interest rates, too much debt, and structural constraints. To make microfinance work better in rural India, policy suggestions include controlling interest rates, teaching people how to manage their money, and building better infrastructure.